Evaluation of pre- and post-fusion Human metapneumovirus F proteins as subunit vaccine candidates in mice. Issue 9 (24th February 2020) - Pilaev, Martin; Shen, Yao; Carbonneau, Julie; Venable, Marie-Christine; Rhéaume, Chantal; Lavigne, Sophie; Couture, Christian; Guarné, Alba; Hamelin, Marie-Ève; Boivin, Guy
Abstract: Human metapneumovirus (hMPV) is an important respiratory pathogen especially in young children and elderly subjects. Our objective was to assess the immunogenicity and protection conferred by predominant pre- and post-fusion (F) hMPV-F constructs in Balb/C mice. Immunizations without adjuvant were not immunogenic whereas alum-adjuvanted hMPV-F proteins, regardless of their conformations, generated comparable neutralizing antibody titers with undetectable pulmonary viral titers following viral challenge. In conclusion, we found no apparent advantage for mixtures of predominant pre-fusion F proteins over post-fusion conformations for hMPV vaccination in opposite to recent data obtained with the human respiratory syncytial virus.